77. Opportunity for Improved Use of a Commercially Available Meningitis/Encephalitis Panel in Pediatric Patients. (4th December 2021) - Valentine, Marilyn E; Olson, Jared; Thorell, Emily A; Bonkowsky, Anne; Lake, Jason
Abstract: Background: The BioFire® FilmArray Meningitis/Encephalitis (ME) panel delivers timely CSF analysis when meningitis or encephalitis is suspected and has the potential for earlier optimization of patient care. It is unclear if the M/E panel provides incremental benefit over standard microbiologic methods such as culture and cell counts, especially in the absence of significant pleocytosis. We evaluated the clinical utility of the ME panel with respect to CSF white blood cell count per high power field (WBC/hpf) and patient age. Methods: We identified paired CSF ME panels and CSF cultures collected throughout a large healthcare system from 2016–May 2021 in children < 18 years of age. CSF results from the same calendar day were included in the dataset. We reviewed standalone HSV and Enterovirus (EV) CSF studies to determine frequency of duplicative testing. Results were stratified by CSF WBC/hpf and patient age (< 14 days, 14–60 days, > 60 days and < 5 years, and > 5 years). Results: 1045 paired cultures and ME panels were identified. Of those, 921 (88%) ME panels were negative, but 5 of those cultures grew bacteria. Of 124 (12%) positive ME panel results, 66% were viral: 46 (37%) EV, 22 (18%) HHV-6 and 6 (5%) parechovirus. In 498 cases, ME panels were sent when CSF had < 10 WBC/hpf, resulting in only 2 (0.4%) PCRs positive for bacteria, one which was gram stain positive and the other was considered a false positive (Table 1). In addition to a ME panel, standalone PCRs for enterovirus and HSV were sent in 134 (13%) and 213 (20%) of cases, respectively, with < 2% discordance. Pathogen distribution by ME panel did not vary with age (Table 2). Meningitis and encephalitis panel, standalone PCR and culture results overall and by age group. Conclusion: In our cohort, the ME panels were overwhelmingly negative. Only 12% of ME panels were positive, mostly with self-limited viral pathogens (e.g., EV, parechovirus). Performance was worse when samples had < 10 WBC/hpf. Duplicative testing was common and had no benefit. Performance was similar across age groups. More targeted use of the ME panel could improve the utility and efficacy of this test. Disclosures: Anne Bonkowsky, MD/PhD, BioFire Diagnostics (Consultant, Grant/Research Support, Other Financial or Material Support, I have intellectual property through the University of Utah in BioFire Diagnostics and the FilmArray and receive royalties through the University of Utah.)Merck (Advisor or Review Panel member)